Level of emotional intelligence and work stress in hospital nurses I - La Libertad Essalud care network (SCIÉNDO INGENIUM, 2021)
This descriptive correlational investigation, it made since January and December 2019. The purpose was to determine relationship between the level of emotional Intelligence and Work Stress in 94 nurses at hospitals level I La Libertad Healthcare Networkm. The Bar on emotional Intelligence questionnaire and the questionnaire to work Stress based on The Nursing Stress Scale by Pamela Graay Toft y James G were used as instruments. The information so far entered and processed in program IBM SPSS STATISTICS version 25, the results are presente in single and double entry tablets, to determine if there is a relationship between variables, The Pearson correlation test was used considering that there is suficiente evidence of statistical significance if the probability of have a mistake is less than 5 percent (p≤0.05), being 0.001 for what he considers highly significant and also the normality of the data was carried out with the proof of Kolmogorov smirnov. The folowing results are reached as obtained:  64.9 percent of nurses have a highly developed and adequate level of emotional intelligence, 46.8 percent have a high level of Work Stress. There conclution is significant relationship between level of emotional Intelligence and work Stress.
Keywords: Emotional Intellectuality; Work Stress; Nurse